Integration of a singularly perturbed degenerate linear system - Starun, I. I.; ShkiI, N. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We present a method for finding a solution of a linear homogeneous system with degenerate matrix and a small parameter with the derivative.